Communities and place : a thematic approach to the histories of LGBTQ communities in the United States - Crawford-Lackey, Katherine; Springate, Megan E. (Berghahn Books, 2020)
"Lesbian, gay, bisexual, transgender, and queer (LGBTQ) people have established gathering spaces to find acceptance, form social networks, and unify to resist oppression. Framing the emergence of queer enclaves in reference to place, this volume explores the physical and symbolic spaces of LGBTQ Americans. Authors provide an overview of the concept of "place" and its role in informing identity formation and community building. The book also includes interactive project prompts, providing opportunities to practically apply topics and theories discussed in the chapters"--